Challenging the Architecture: a Critical History of the Wisconsin Prison System - (:unkn) unknown (My University, 2019)
In my dissertation I explore the history of the Wisconsin prison system, with an emphasis on 1970 to 2019, Waupun Correctional Institution and Taycheedah Correctional Institution. From this study, I explore the nature of the Wisconsin system and how it has developed. Across this work I argue that the core priority for the WI Department of Corrections has been to maintain and expand its bureaucratic infrastructure, imposing limited recourse on prisoners, and maximizing its own disciplinary flexibility. There have been significant human costs to this system, and my work helps to document these costs, contextualize why they happened, and look at the resistance prisoners have made against the Wisconsin carceral regime.
Keywords: history; prison; slavery